Magna Carta, religion and the rule of law / edited by Robin Griffith-Jones and Mark Hill QC. - Griffith-Jones, Robin; Hill, Mark, 1965- (Cambridge University Press, 2015)
Archbishop Stephen Langton hoped with Magna Carta to realise an Old Testament, covenantal kingship in England. At the Charter's 800th anniversary, distinguished jurists, theologians and historians from five faith-traditions and three continents ask how Magna Carta's biblical foundations have mattered and still matter now. A Lord Chief Justice, a Chief Rabbi, a Grand Mufti of Egypt, specialists in eight centuries of law, scholars and advocates committed to the rule of law and to the place of religion in public life all come together in this testimony to Magna Carta's iconic power. We follow the Charter's story in the religious life of the UK, America and now Continental Europe, and reflections on religio-legal traditions far from the Common Law enrich the story. Magna Carta, Religion and the Rule of Law invites all religions to ask what contribution they themselves should make to the rule of law in today's secular, democratic polities.